PENGARUH PENAMBAHAN BAHAN KIMIA PADA TANAH LEMPUNG TERHADAP KUAT KOMPRESIF TAK TERKEKANG - Anita Setyowati Srie Gunarti (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2010)
Land is a very complex material. We must improve physical and mechanical properties of the soil if it is found that the soil does not meet the technical requirements to be used to support buildings or roads. Therefore, before using it as a support building, the ground must be stabilized. One method for stabilizing the soil is chemical stabilization as an effort to increase strength, reduce declination, and improving physical and mechanical properties of others. In this study, we use chemical stabilization method to perform a series tests of physical properties and compressive strength test on the land unfettered native land and soil soaked with a chemical solution between the Na2C03, CaCl2, KOH, and Na2Si03 (Water-glass) as much as 2 g / liter for 24 hours at the Laboratory of Soil Mechanics of Unisma Bekasi and Soil Mechanics Laboratory of the Public Works Department of Irrigation at Central Jakarta Physical properties of a series of tests concluded that the soil has a high development and graded poorly because it does not meet the criteria for the coefficient of gradation and uniformity coefficient. Land, including the type CH (inorganic clay with high plasticity), and within the category of very soft clay and a bit sensitive. The test results unleashed a strong compressive (qu), the highest value obtained on clay soaked in a solution ofpotassium hydroxide (KOH) 2 g/liter is equal to 84.21% of the value ofquof original land